Physical Inactivity - Do We Hit Rock Bottom? The Epidemiology and Impact of Physical Activity and Sedentary Behaviour in Adults - Rostkowska, Aneta; Kupisiak, Sebastian; Draim, Malwina; Pasierb, Natalia; Rękas, Barbara; Kosowska, Michalina; Dzierzgowska, Wiktoria (Quality in Sport, 2024)
Introduction and purpose Physical activity protects both physical and mental health. However, widespread physical inactivity is the leading risk factor for global mortality. Despite the promotion of healthy lifestyle, there has been no improvement in global levels of physical activity since 2001. This review aims to present the prevalence of physical activity and inactivity across Poland, the European Union (EU) and the world. This cross-national compilation can be used to create campaigns to raise social awareness around physical activity as well as to help health-care providers encourage patients to limit sedentary time. It provides a reliable comparison and indicates vulnerable points regarding the physical activity levels in our societies that should be monitored in further researches. Additionally, there is a summary of the most important health benefits associated with being more active and health risks arising from prolonged sitting time. Brief description of the state of knowledge World Health Organization (WHO) recommends adults to do at least 150 minutes of moderate-intensity, or 75 minutes of vigorous-intensity physical activity per week (or an equivalent combination of the two). Globally, more than 1 in 4 adults are insufficiently physically active. Summary If current trends in insufficient physical activity continue, the global target of a 15% relative reduction between 2018 and 2030 will not be met for adults. Investing in policies to promote active recreation and transport, creating affordable and safe spaces and conducting national and community-based campaigns play a key role in limitting sedentary behaviour and increasing physical activity.